Starting over in Eastern Europe - "Johnson, Simon" (Boston, 1995)
How will Poland and its neighbors transform their economies after communism? Contrary to traditional wisdom, the authors argue that new private business rather than restructured state enterprises will be the main engine of economic renewal throughout the region. Case studies from Poland's shipbuilding, clothing, consulting, food, banking, and publishing industries contrast strategic successes and failures and illustrate the tremendous energy and potential of a rising entrepreneurial class. Ultimately, the authors suggest, reallocation of resources via the creation of new businesses will be the key to sustained domestic growth and international competitiveness for post-communist countries.
Keywords: Poland-Economic policy